Critical Factors Affecting the Quality Management System in Oil & Gas On-Shore Drilling Sector for In-Sourcing Drilling Model. - Ali Malik, Al Harthy; Hock, Oo Yu; Said M., Al-Saqri; Asif, Mahbub Karim (2018)
The intention of this research is to define the critical variables which are affecting the overall quality management system and develop a sustainable quality management system (SQMS) for Oil and Gas sector, specifically for On-shore drilling operations, by which it will enhance the overall performance for the In-Sourcing drilling model. However, the intention of this paper (Part-1) is to demonstrate the road map of developing the conceptual framework which is driven from other different quality theoretical frameworks and models (where it was concluded after a comprehensive literature review that there is no fit for purpose QMS in a specific sector, instead companies depend on generic frameworks such as ISO: 9001, etc). The concluded results are that conceptual framework consists of in-dependent variables which are (competency framework, preventive maintenance, management of change (MOC) and people recognition and dependent variable which is the overall performance by establishing a sustainable quality management system. The author used the Total Quality Management (TQM) model (focusing on three areas which are technology and digitalization assurance and lean) to study the effect of independent variable on the overall performance. In part 2, all the sampling and data analysis will be demonstrated to confirm the proposed conceptual framework as described in part1.